2006
DOI: 10.1128/cmr.00051-05
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia: Diagnosis, Treatment, and Prevention

Abstract: SUMMARY While critically ill patients experience a life-threatening illness, they commonly contract ventilator-associated pneumonia. This nosocomial infection increases morbidity and likely mortality as well as the cost of health care. This article reviews the literature with regard to diagnosis, treatment, and prevention. It provides conclusions that can be implemented in practice as well as an algorithm for the bedside clinician and also focuses on the controversies with regard to diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
321
0
31

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(361 citation statements)
references
References 232 publications
(217 reference statements)
9
321
0
31
Order By: Relevance
“…A PAVM também parece incidir mais frequentemente em pacientes acometidos pela síndrome da angústia respiratória aguda (SARA). 2,5,[9][10][11][12][13][14][15] PAVM representa um grande desafio diagnóstico e terapêutico em função da ausência de um padrão ouro bem definido para seu diagnóstico, e do uso inadequado de antimicrobianos. São necessários vários parâmetros (clínicos, laboratoriais e de imagem) para confirmar a presença dessa patologia.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A PAVM também parece incidir mais frequentemente em pacientes acometidos pela síndrome da angústia respiratória aguda (SARA). 2,5,[9][10][11][12][13][14][15] PAVM representa um grande desafio diagnóstico e terapêutico em função da ausência de um padrão ouro bem definido para seu diagnóstico, e do uso inadequado de antimicrobianos. São necessários vários parâmetros (clínicos, laboratoriais e de imagem) para confirmar a presença dessa patologia.…”
Section: Introductionunclassified
“…Os sinais radiológicos levam a 20 a 25 % de resultados falso-positivos e 30 a 35% de falso--negativos, devido a possibilidades de outras patologias causarem alterações semelhantes. 1,2,5,11,16,17 Um dos indicadores prognósticos mais utilizados em UTI é o Acute Physiology and Cronic Health Evaluation II (APACHE II) que estabelece a gravidade e risco de morte em pacientes hospitalizados. O conjunto de modelos APACHE tem sido atualizado desde finais dos anos 70.…”
Section: Introductionunclassified
“…Ventilatör ilişkili pnömoni mortalitesi yapılan yayın-larda %0 ile %50 arasında değişmektedir (4). Mortalite oranındaki bu farklılık çalışmaların farklı grup hastalarda yapılmış olmasıdır.…”
Section: Introductionunclassified
“…Akut respiratuar distres sendromlu (ARDS) hastalarda klinik kriterlerin duyarlılığı düşmektedir. Çünkü bu hastalarda akciğer grafisinde pnömoniye ait infiltratları ayırt etmek zordur ve yalancı negatiflik oranı %46'ları bulmaktadır (4). Artmış pürülan balgam, balgam kültür pozitifliği, ateş ve lökositoz varlığında akciğer grafisinde infiltrasyon olmazsa trakeobronşit tanısı olmaktadır.…”
Section: Introductionunclassified
“…In the setting of ARDS, Bell et al reported a false negative rate of 46% for the clinical diagnosis of VAP. [19] Also, a study conducted by Jean et al showed that, 55% of the patients with ARDS develop VAP, as compared to 28% of the patients without ARDS. Thus, microbiological evaluation in the form of quantitative, invasive or non-invasive techniques helps in early diagnosis of VAP in patients with ARDS.…”
Section: Jmscr Vol||06||issue||05||page 927-933||may 2018mentioning
confidence: 99%